A comparative study of image processing thresholding algorithms on residual oxide scale detection in stainless steel production lines - Cañero-Nieto, Juan Miguel; Solano-Martos, José Francisco; Martín-Fernández, Francisco de Sales (My University, 2019)
The present work is intended for residual oxide scale detection and classification through the application of image processing techniques. This is a defect that can remain in the surface of stainless steel coils after an incomplete pickling process in a production line. From a previous detailed study over reflectance of residual oxide defect, we present a comparative study of algorithms for image segmentation based on thresholding methods. In particular, two computational models based on multi-linear regression and neural networks will be proposed. A system based on conventional area camera with a special lighting was installed and fully integrated in an annealing and pickling line for model testing purposes. Finally, model approaches will be compared and evaluated their performance..